2020
DOI: 10.1108/lht-07-2020-0178
|View full text |Cite
|
Sign up to set email alerts
|

How to protect reader lending privacy under a cloud environment: a technical method

Abstract: PurposeIn this paper, the authors propose an effective mechanism for the protection of digital library readers' lending privacy under a cloud environment.Design/methodology/approachThe basic idea of the method is that for each literature circulation record, before being submitted to the untrusted cloud database of a digital library for storage, its reader number has to be encrypted strictly at a client, so as to make it unable for an attacker at the cloud to know the specific reader associated with each circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Cloud computing has been developed quickly. 175,176 It has attracted high acceptance as a computing paradigm across the world due to its benefits: fast arrangement, low cost (on installation and optimization), huge storing capacity, and easy on-demand access to the system. [177][178][179] We found that the highest number of published articles is for 2012; the lowest is for 2016 and 2017 based on the performed SLR from 2012 to the end of 2019.…”
Section: Results and Comparisonsmentioning
confidence: 99%
“…Cloud computing has been developed quickly. 175,176 It has attracted high acceptance as a computing paradigm across the world due to its benefits: fast arrangement, low cost (on installation and optimization), huge storing capacity, and easy on-demand access to the system. [177][178][179] We found that the highest number of published articles is for 2012; the lowest is for 2016 and 2017 based on the performed SLR from 2012 to the end of 2019.…”
Section: Results and Comparisonsmentioning
confidence: 99%
“…However, there is still another important issue which have not been addressed in combinatorial t-way testing known as privacy protection. An individual's or a group's ability to seclude themselves or information about themselves, and therefore express themselves selectively, is known as privacy [323], [324], [325]. The concept of responsible use and protection of information falls under the area of privacy, which is partially overlapped with security [325].…”
Section: Discussionmentioning
confidence: 99%
“…Since the early days of basic file sharing and hosting of distributed applications on servers, the types of network problems have changed dramatically [7]. Recently, organizations are increasingly employing advanced computing systems to satisfy their requirements, including cloud-based systems, virtualized resources, servers, and remote storage that need extra computing resources, work, and arrangement [8,9]. However, despite their pervasive adoption, traditional IP-based networks are complex and challenging to manage.…”
Section: IImentioning
confidence: 99%